2019
DOI: 10.1111/1750-3841.14818
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Antibiotic Resistance Genes in Marketed Ready‐to‐Eat Small Crickets (Acheta domesticus)

Abstract: The present investigation was aimed at evaluating the occurrence of transferable genes conferring resistance to tetracyclines, macrolide‐lincosamide‐streptogramin B (MLSB), vancomycin, beta‐lactams, and aminoglycosides in 32 samples from eight batches of ready‐to‐eat crickets (Acheta domesticus) commercialized by four European Union producers (two batches per producer). Bacterial DNA extracted directly from the insects was subjected to optimized polymerase chain reaction (PCR) and nested‐PCR assays for the qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…In food industries in Europe, a recent study has revealed antibiotic resistant genes in A. domesticus. As a preventive measure, Roncolini et al [ 163 ] suggested standardization of the production processes and a prudent use of antimicrobials during the rearing of edible insects. Even though Spiroplasma sp.…”
Section: Insect Qualitymentioning
confidence: 99%
“…In food industries in Europe, a recent study has revealed antibiotic resistant genes in A. domesticus. As a preventive measure, Roncolini et al [ 163 ] suggested standardization of the production processes and a prudent use of antimicrobials during the rearing of edible insects. Even though Spiroplasma sp.…”
Section: Insect Qualitymentioning
confidence: 99%
“…The samples that were negative for each of the AR genes under study were further subjected to nested PCR assays designed to enhance the gene detection sensitivity, as previously reported by Garofalo et al [31]. The high sensitivity of the latter method was confirmed in recent studies aimed at detecting the same AR genes in different edible insects [14,16,17,19,20] as well as in human stool and saliva samples [30,33].…”
Section: Discussionmentioning
confidence: 78%
“…The primers used for the PCR and nested PCR as well as the thermal cycling conditions for all but the aac-aph gene were as previously reported by Milanović et al [30], while the PCR conditions for the latter gene were detailed by Garofalo et al [31]. DNA was extracted from 12 bacterial reference strains [16,17,19,20], each carrying one of the AR genes under study, and they were used as positive controls in each PCR and nested PCR assay, whereas the DNA extracted from Enterococcus faecalis JH2-2 [32] was used as a negative control. Furthermore, a blank control containing molecular biology grade water instead of DNA was used in each assay to exclude the presence of PCR contaminants.…”
Section: Detection Of Ar Genes By Pcr and Nested Pcrmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, an investigation aiming at evaluating the occurrence of ARGs in crickets provided evidence that deliberately used or naturally occurring antibiotics were selective pressure on the microbiota of insects (Roncolini et al. 2019). ARBs were also isolated from ants, flies, spiders, cockroaches, and moths (Hassan et al.…”
Section: Transmission Of Args Mediated By Honeybeesmentioning
confidence: 99%